Ebu Bekir İbnü’l-Arabi ve el-Emedü’l-Aksa adlı eseri : (Esma-i hüsna ve sıfatullah bahislerinin edisyon kritik, tahkik ve değerlendirilmesi) - Biçer, Ramazan (My University, 1999)
In this study, which is entitled Abu Bekir Ibn Al-Arabi and his work al-Amad al-aqsa first of all we established the author's views on the names and attributes of God. The study cosists of one introduction and two main sections. In the introduuction of the thesis we analysed the political and cultural conditions of the age in which the authour lived. Then we turned to examine his theological views. In the first section of the thesis we analysed the author's views on the attributes of God in a comparative way. In the second section in uhich the names of God and the related problems were dealt, we examined the author's views on the subjcet in relation to the views of his contemporaries and predecessors. A part from making an ausessement at the end of every section, we also made a general ausessment at the end of thecis under the name of coclusion. We are of the opinion that Ibn al-Arabi who pret great emphasis on intelligence and freedom of thought in tacling the religious issues end problems, has an important place in Islamic litterature.
Keywords: Din; EBU BEKİR İBNÜ’L ARABİ -BİYOGRAFİ; EBU BEKİR İBNÜ’L ARABİ -GÖRÜŞLERİ; İslam Dini; İslam mezhepleri ve reform hareketleri; Sünnî mezhepler